2020
DOI: 10.3390/ijerph17134630
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Myths about Palliative Care among the General Public and Health Care Professionals in Portugal

Abstract: Background: International research has shown that healthcare professionals (HCPs) and nonhealthcare professionals (NHCPs) are unaware of the goals and purposes of palliative care. This study evaluates the knowledge of palliative care among a sample of Portuguese adults and correlates their level of knowledge with age, gender, profession, and experience of family member’s palliative care. Method: A cross-sectional online survey was carried out on a sample of 152 HCPs and 440 NHCPs who completed an anonymous que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…There is strong evidence in the literature that unresolved misconceptions about palliative care create barriers to the provision of this type of care. [15,18] Therefore, it is of crucial importance to discuss and deal with it for a good palliative care provision. [15] Strategies addressing misperceptions surrounding PPC are needed to reduce barriers affecting the delivery of this type of care and improve its accessibility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is strong evidence in the literature that unresolved misconceptions about palliative care create barriers to the provision of this type of care. [15,18] Therefore, it is of crucial importance to discuss and deal with it for a good palliative care provision. [15] Strategies addressing misperceptions surrounding PPC are needed to reduce barriers affecting the delivery of this type of care and improve its accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…[15,18] Therefore, it is of crucial importance to discuss and deal with it for a good palliative care provision. [15] Strategies addressing misperceptions surrounding PPC are needed to reduce barriers affecting the delivery of this type of care and improve its accessibility. [16] However, a few studies suggested strategies to overcome these erroneous representations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations